A potential community-based tourism analysis of Baseco: A basis for socio-economic sustainability development - De Leon, Shaira Mae; Tero, Lou Frenila; Sayago, Nikki Pauline; Fortis, James Andrew; Revellame, Ethel Fhaye; Cruz, Merceditas Dela (Journal of Sustainability, Society, and Eco-Welfare, 2024)
Background: Community-based tourism has been promoted as a strategy for the reduction of poverty, with the potential to improve the sustainability of marginalized regions and communities. The locals of Baseco have low wages, unsecured employment, and limited access to primary services like education, healthcare, sanitation, and adequate shelter. Methods: The study determines the relationship between the local government views on community-based tourism and their level of contributions to the community-based tourism for the Baseco’s socio-economic sustainability development. The researchers had two distinct categories of respondents to get the perspectives of all parties involved in the study’s beneficial result. Using the quantitative method and the purposive sampling technique, there were 130 respondents through online survey questionnaires. The data of the respondents were examined using a Likert scale, and the collected information was statistically analyzed using frequency, weighted mean, standard deviation, and Pearson correlation coefficient. Finding: Using the elements of community-based tourism such as: (1) resource conservation; (2) social and economic development; (3) empowerment and ownership; and (4) quality visitor experience, the participants determine the impact of community-based tourism to the community. The result indicates a moderately strong positive relationship between the viewed community-based tourism socio-economic activity of the local government unit in Baseco and the perceived level of possible contributions to its community-based socio-economic sustainability. Moreover, the result from the local community of Baseco indicates a strong agreement and satisfaction with the possible implementation of community-based tourism in Baseco. Conclusion: The residents firmly support and express pleasure with the implementation of community-based tourism as shown in the data.